Strategi Guru Dalam Menanamkan Sikap Sosial Siswa Kelas V SDIT Al-Hidayah Pekanbaru - ., Soleha; ., Siti Quratul Ain (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The purpose of this study was to find out how the teacher's strategy in instilling social attitudes in class V SDIT Al- Hidayah Pekanbaru. This type of research is a qualitative research using a qualitative descriptive method which takes place at SDIT Al-Hidayah Pekanbaru. The sample in this study were fifth grade students at SDIT Al-Hidayah Pekanbaru. The data collection instruments used in this study consisted of interviews, observations and documentation which were then analyzed with reference to the Miles and Huberman method. The results of this study are the teacher's strategy in instilling students' social attitudes through four ways, namely habituation patterns, pilot patterns, spontaneous activities and admonishing or advising. The pattern of habituation is carried out by accustoming students to religious activities, accustoming students to obeying the rules, and habituating students to behave and say good things. The pilot pattern is carried out by the teacher by exemplifying students obeying the rules and exemplifying good behavior and speech. Spontaneous activities are carried out by the teacher to reprimand directly when students commit wrong actions and give praise when students successfully complete assignments properly. Reprimanding and advising teachers do when students violate class and school rules.